Extramammary Paget's Disease of the Vulva: A Rare Case Report - Pancakarsa, Eka Prasetya; Kiki Ahmad Rizki; Monty P. Soemitro; Maman Abdurahman; Yohana Azhar; Dodi L. H. L. Gaol (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Extramammary Paget’s Disease (EMPD) is a rare disease characterized by intraepithelial involvement of the skin by non-squamous carcinoma cells in areas containing apocrine glands such as the vulva, perineum, perianal area, scrotum, and penis. Case presentation: A 48 year old woman complained of a non-healing wound in the genital area for 1 year. The wound feels painful and does not bleed easily. No lumps were found anywhere else. The patient works as a private employee with minimal exposure to sunlight. No history of trauma. There is a history of surgical biopsy with the result of a malignant tumor with an impression Extramammary Paget Disease. Conclusion: We present a case of a rare malignant tumor with EMPD impression of the vulva, extending to the perineum and suprapubic.